Inflammasome targeted therapy as novel treatment option for aortic aneurysms and dissections: a systematic review of the preclinical evidence - Wortmann, Markus; Klotz, Rosa; Kalkum, Eva; Dihlmann, Susanne; Böckler, Dittmar; Peters, Andreas (Frontiers in Cardiovascular Medicine, 2022)
Both aortic aneurysm and dissection are life threatening pathologies. In the lack of a conservative medical treatment, the only therapy consists of modifying cardiovascular risk factors and either surgical or endovascular treatment. Like many other cardiovascular diseases, in particular atherosclerosis, aortic aneurysm and dissection have a strong inflammatory phenotype. Inflammasomes are part of the innate immune system. Upon stimulation they form multi protein complexes resulting mainly in activation of interleukin-1β and other cytokines. Considering the gathering evidence, that inflammasomes are decisively involved in the emergence and progression of aortic diseases, inflammasome targeted therapy provides a promising new treatment approach. A systematic review following the PRISMA guidelines on the current preclinical data regarding the potential role of inflammasome targeted drug therapy as novel treatment option for aortic aneurysms and dissections was performed. Included were all rodent models of aortic disease (aortic aneurysm and dissection) evaluating a drug therapy with direct or indirect inhibition of inflammasomes and a suitable control group with the use of the same aortic model without the inflammasome targeted therapy. Primary and secondary outcomes were incidence of aortic disease, aortic rupture, aortic related death, and the maximum aortic diameter. The literature search of MEDLINE (via PubMed), the Web of Science, EMBASE and the Cochrane Central Registry of Registered Trials (CENTRAL) resulted in 8,137 hits. Of these, four studies met the inclusion criteria and were therefore eligible for data analysis. In all of them, targeting of the NOD-, LRR- and pyrin domain-containing protein 3 (NLRP3) inflammasome effectively reduced the incidence of aortic disease and aortic rupture, and additionally reduced destruction of the aortic wall. Treatment strategies aiming at other inflammasomes could not be identified. In conclusion, inflammasome targeted therapies, more precisely targeting the NLRP3 inflammasome, have shown promising results in rodent models and deserve further investigation in preclinical research to potentially translate them into clinical research for the treatment of human patients with aortic disease. Regarding other inflammasomes, more preclinical research is needed to investigate their role in the pathophysiology of aortic disease.Protocol Registration: PROSPERO 2021 CRD42021279893, https://www.crd.york.ac.uk/prospero/display_record.php?ID=CRD42021279893